ADVOKASI WOMEN’S INTERNATIONAL LEAGUE FOR PEACE AND FREEDOM TERHADAP KEKERASAN SEKSUAL PEREMPUAN DI SURIAH TAHUN 2020 – 2024 - Delfi Riska Ananda; Arif Wicaksa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The armed conflict in Syria since 2011 has caused a severe humanitarian crisis, including sexual violence against women used systematically as a weapon of war by various warring parties. The Syrian Network for Human Rights (SNHR) documented at least 11,553 incidents of sexual violence against women since the conflict began, with the majority perpetrated by Assad regime forces. This situation prompted the active involvement of the Women's International League for Peace and Freedom (WILPF) as a transnational feminist organization to advocate for women's protection and demand accountability at the international level. This study employs a qualitative descriptive method with library research as the data collection technique. The analysis was conducted using a transnational feminist perspective and the Transnational Advocacy Networks (TANs) theory by Keck and Sikkink with a group level of analysis, to examine WILPF's advocacy strategies against sexual violence toward women in the Syrian conflict during the period of 2014–2024. The findings reveal that WILPF implemented four integrated strategies in accordance with TANs theory: information politics through documentation and publication of reports, symbolic politics through amplifying survivors' voices in international forums, leverage politics through lobbying UN member states and engaging with international human rights mechanisms, and accountability politics through advocating for transitional justice and demanding perpetrator accountability. These strategies were carried out through a Local-Global-Local approach that connects the experiences of Syrian women at the local level with global policy forums. Despite facing significant obstacles including limited access, social stigma, repression by conflicting parties, and weak international accountability mechanisms, WILPF has consistently worked toward recognizing sexual violence as an international security issue requiring comprehensive political and legal responses. Keywords: Advocacy, WILPF, Sexual Violence, Syrian Conflict, Transnational Advocacy Networks